Feminisme Masa Kolonialisme: Representasi Perempuan pada Karakter Nyai Ontosoroh dalam Film Bumi Manusia: Indonesia - Dwi Aryani, Nur Luthfia (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2023)
This study discusses the film Bumi Manusia with the historical, colonial and historical genres that have their own artistic appearance, this film carries the value of feminism in representing women. This feminist ideology gives rise to awareness of the desire of women from all walks of life to get the same rights as men and to be free from acts of racism, stereotypes, hegemony, domination and violence that are widely practiced in society. The purpose of the study was to determine how the representation of colonial women's feminism is depicted in the character of Nyai Ontosoroh in the film Bumi Manusia. This study uses a descriptive qualitative method with Sara Mills' critical discourse analysis. Data analysis techniques by collecting and analyzing data, categorizing subject-object positions, conducting Sara Mills' critical discourse analysis and making conclusions based on the results of the analysis. From the results of this study it can be concluded that the representation of women in the character of Nyai Ontosoroh in the film Bumi Manusia, where it is stated that women are depicted through the subject position held by other characters in the film, the director or the writer of the adaptation of the film which is a novel with the same title. Women are represented as having courage that is in line with the values ??of feminism itself. There are several parties who try to destroy the feminist agent in women, which triggers resistance from parties who have the same school of thought and understanding. Nyai Ontosoroh has great courage to oppose the injustices that continue to come to her. The courage shown actually has a positive value, but many parties oppose this courage. Keywords: Film, Representation, Feminism, Bumi Manusia, Sara Mills' discourse analysis